Studies in Political Humour : In between political critique and public entertainment. - Tsakona, Villy; Popa, Diana Elena (Discourse approaches to politics, society, and culture, 2011)
If politics is a serious matter and humour a funny one, this volume investigates how and why the boundaries between the two are blurred: politics can be represented in a humorous manner and humour can have a serious intent. Political humour conveys criticism against the political status quo and/or recycles and reinforces dominant views on politics. The data analysed comes from European states with different sociopolitical histories and traditions and the methodologies adopted originate in different fields (discourse analysis, folklore and cultural studies, media studies, sociolinguistics, sociology, theatre semiotics). The first part of the volume is dedicated to politicians' humour as a means of public positioning, deliberation, and eventually attack against political adversaries, while the second one involves political satire as realised in different genres: animation, impersonation, and cartoons. Last but not least, the third part shows how political humour can be manipulated in public debates or become an integral part of postmodern art.